A complex rearrangement associated with sex reversal and the Wolf-Hirschhorn syndrome: a cytogenetic and molecular study. Issue 6 (June 1992) - Coles, K; Mackenzie, M; Crolla, J; Harvey, J; Starr, J; Howard, F; Jacobs, P
Abstract : We report a male infant referred with multiple congenital abnormalities consistent with the Wolf-Hirschhorn syndrome. Cytogenetic analysis showed a chromosome complement of 46, XX with a deletion of 4p15.2—-4pter and its replacement by material of unknown origin. The patient was positive for a number of Yp probes including SRY, the testis determining factor, and in situ hybridisation localised the Yp material to the tip of the short arm of one X chromosome. Using pDP230, a probe for the pseudoautosomal region, and M27 beta, which recognises a locus in proximal Xp, the material translocated on to 4p was identified as originating from the short arm of the paternal X chromosome. The most reasonable explanation for this complex rearrangement is two separate exchange events involving both chromatids of Xp during paternal meiosis. An aberrant X-Y interchange gave rise to the sex reversal and an X;4 translocation resulted in additional, apparently active Xp material and a deletion of 4p which produced the Wolf-Hirschhorn phenotype.